Influence of caffeine on perception of effort, metabolism and exercise performance following a high-fat meal - Hadjicharalambous, M.; Georgiades, E.; Kilduff, L. P.; Turner, A. P.; Tsofliou, F.; Pitsiladis, Y. P. (Journal of Sports Sciences, 2006)
This study examined the effects of caffeine, co-ingested with a high fat meal, on perceptual and metabolic responses during incremental (Experiment 1) and endurance (Experiment 2) exercise performance. Trained participants performed three constant-load cycling tests at approximately 73% of maximal oxygen uptake (&Vdot;O2max) for 30 min at 20°C (Experiment 1, n = 8) and to the limit of tolerance at 10°C (Experiment 2, n = 10). The 30 min constant-load exercise in Experiment 1 was followed by incremental exercise (15 W · min-1) to fatigue. Four hours before the first test, the participants consumed a 90% carbohydrate meal (control trial); in the remaining two tests, the participants consumed a 90% fat meal with (fat + caffeine trial) and without (fat-only trial) caffeine. Caffeine and placebo were randomly assigned and ingested 1 h before exercise. In both experiments, ratings of perceived leg exertion were significantly lower during the fat + caffeine than fat-only trial (Experiment 1: P < 0.001; Experiment 2: P < 0.01). Ratings of perceived breathlessness were significantly lower in Experiment 1 (P < 0.01) and heart rate higher in Experiment 2 (P < 0.001) on the fat + caffeine than fat-only trial. In the two experiments, oxygen uptake, ventilation, blood [glucose], [lactate] and plasma [glycerol] were significantly higher on the fat + caffeine than fat-only trial. In Experiment 2, plasma [free fatty acids], blood [pyruvate] and the [lactate]:[pyruvate] ratio were significantly higher on the fat + caffeine than fat-only trial. Time to exhaustion during incremental exercise (Experiment 1: control: 4.9, s = 1.8 min; fat-only: 5.0, s = 2.2 min; fat + caffeine: 5.0, s = 2.2 min; P > 0.05) and constant-load exercise (Experiment 2: control: 116 (88 - 145) min; fat-only: 122 (96 - 144) min; fat + caffeine: 127 (107 - 176) min; P > 0.05) was not different between the fat-only and fat + caffeine trials. In conclusion, while a number of metabolic responses were increased during exercise after caffeine ingestion, perception of effort was reduced and this may be attributed to the direct stimulatory effect of caffeine on the central nervous system. However, this caffeine-induced reduction in effort perception did not improve exercise performance.